2006
DOI: 10.1128/jb.188.7.2463-2472.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Peptidoglycan Mediates Lysostaphin Binding to the Cell Wall Envelope ofStaphylococcus aureus

Abstract: Staphylococcus simulans bv. staphylolyticus secretes lysostaphin, a bacteriocin that cleaves pentaglycine cross bridges in the cell wall of Staphylococcus aureus. The C-terminal cell wall-targeting domain (CWT) of lysostaphin is required for selective binding of this bacteriocin to S. aureus cells; however, the molecular target for this was unknown. We used purified green fluorescent protein fused to CWT (GFP-CWT) to reveal speciesspecific association of the reporter with staphylococci. GFP-CWT bound S. aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
138
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 72 publications
7
138
1
Order By: Relevance
“…3). These findings are similar to the results obtained with lysostaphin and ALE-1, a glycyl-glycine endopeptidase homologous to lysostaphin, which showed a (1,22), which bind to cross-linked peptidoglycan and recognize the Gly 5 interpeptide cross bridge (12,22). Our results suggest that a similar targeting mechanism exists for the 11 endolysin and that, in this respect, the phage enzyme closely resembles its staphylococcal counterparts.…”
supporting
confidence: 79%
“…3). These findings are similar to the results obtained with lysostaphin and ALE-1, a glycyl-glycine endopeptidase homologous to lysostaphin, which showed a (1,22), which bind to cross-linked peptidoglycan and recognize the Gly 5 interpeptide cross bridge (12,22). Our results suggest that a similar targeting mechanism exists for the 11 endolysin and that, in this respect, the phage enzyme closely resembles its staphylococcal counterparts.…”
supporting
confidence: 79%
“…This CBD, shared by lysostaphin (a bacteriocin from Staphylococcus simulans bv. staphylolyticus) and its homologue, hydrolase ALE-1, has been uncovered to recognize pentaglycine cross bridges in PG (68,69). Therefore, the fact that most of the SH3 domains are found in Staphylococcus-like endolysins is not surprising.…”
Section: Resultsmentioning
confidence: 99%
“…Since the killing required contact of the cells, it seemed unlikely that soluble substances, such as bacteriocin (21,60) or killer toxin (53), were involved. We also showed that soluble capsular polysaccharides from C. neoformans inhibited killing.…”
mentioning
confidence: 99%